Assessing Dysphagia in Head and Neck Cancer Patients: Validation and Cultural Adaptation of the Thai M.D. Anderson Dysphagia Inventory (TH-MDADI) - Warut Pongsapich; Narin Ratanaprasert; Prachya Maneeprasopchoke; Paveena Pithuksurachai; Cheerasook Chongkolwatana; Chanticha Chotigavanich; Paiboon Sureepong; Sunun Ongard; Phawin Keskool (Siriraj Medical Journal)
Objective: The validation study of the Thai version of the M.D. Anderson Dysphagia Inventory (TH-MDADI) addresses a critical gap in head and neck cancer (HNC) care in Thailand. At leading institutions like Siriraj Hospital, patient-reported outcomes have been historically neglected, with care primarily focusing on routine medical services. This study aimed to validate the TH-MDADI to enhance dysphagia assessment and promote patient centered care.